FACTORS AFFECTING REVISIT INTENTION WITH CUSTOMER SATISFACTION AS A MEDIATING VARIABLE IN ECO FRIENDLY RESORTS - Syafruddin Chan (Jurnal Manajemen Inovasi, 2018)
this study aimed to observe the effect of concern environment, physical and social environment as an independent variable that affects revisit intention with customer satisfaction as a mediating variable. Questionnaires distributed in eco-friendly resort in Sabang Zone, Indonesia, which is a recreational diving center in western part of Indonesia, using probability sampling techniques. Data were collected and then be analyzed using covariance Based SEM, AMOS. Hypothesis test results proved that there were positive and significant influence among five variables examined in the study, both directly and indirectly. Key words Environment Concern, Physical Environment, Social Environment, Revisit Intention and Customer Satisfaction.